Coloquio: 150 Años del Manifesto Comunista - [Foto Marx und Engels]
politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Kommunismus politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Marxismus soziale Fragen;Kultur und Religion;Kunst;Literatur